Cerebellar syndrome with hydrocephalus due to Mycoplasma pneumoniae infection. Issue 777 (July 1990) - Coleman, R. J.; Brown, J. S.; Butler, P.; Swash, M.
Abstract : A 27 year old woman developed a cerebellar syndrome with serological evidence of recent Mycoplasma pneumoniae infection. The cranial computed tomographic scan showed effacement of the fourth ventricle, enhancement of the basal meninges and hydrocephalus affecting the lateral and third ventricles. Clinical and radiological recovery occurred over 5 weeks. We propose that this was a manifestation of immune-mediated encephalomyelitis induced by the infection rather than direct invasion of the central nervous system.